Pelatihan Pemodelan Instalasi PLTB Sebagai Improve Kurikulum Pengajaran di SMKN 4 Bandung - Wijaya, I Gede Putu Oka Indra; Yustika, Lindiasari Martha; Adam, Kharisma Bani (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
The TSE-Creative Teaching’s Workshop is a community service program by the undergraduate Energy Systems Engineering faculty aimed at sharing knowledge with teachers at SMKN 4 Bandung. This workshop aims to assist teachers in integrating educational technology into their teaching methods. Teachers will learn how to use hardware to install Wind Power Plants (PLTB) and simulate PLTB installations. This aims to enhance the teachers' experience so they can transfer their knowledge to students, preparing them for the clean energy transition in the digital era. During this activity, the teachers achieved an average accuracy of 61% in answering questions correctly. Based on the questionnaire results, 100% of SMKN 4 Bandung participants agreed or strongly agreed on the relevance of the implemented community service program. Through this training, it is expected that teachers will improve their understanding of renewable energy, inspiring and guiding students in understanding the importance of renewable energy and their role in environmental conservation. Additionally, this training is expected to strengthen the school's involvement in sustainable practices and spread awareness about the importance of renewable energy within the local community.